Architecture for Integrating Learning Platforms Using Adapter - Dauda, Ali B; Idris, Abubakar A; Mshelia, Peter Yohanna; Ibrahim, Abdulaziz.I; Umar, Suleman (International Journal of Computer Sciences and Engineering, 2018)
The advantage of the electronic and mobile learning platforms is the dissemination of learning contents with ease. But these platforms operate differently to exchange the learning contents from the server (educator’s site) to the clients (learner’s site). Integrating these learning platforms to operate as a single platform and exchange the contents based on learners’ request could improve the learning efficiency and reduce the operational cost. This work introduces a Web services approach based on client-server model to develop an integrated architecture that join the two learning platforms. In this paper, the architecture of the learning platforms is presented and explained. Furthermore, an adapter in a form of web service is develop as a fuse between the server and the client. Finally, the process of using the web services to unify the two learning architectures using the adapter is demonstrated and explained.